Philip III and the Pax Hispanica, 1598-1621 : the failure of grand strategy - Allen, Paul C., 1964- (Yale historical publications., 2000)
"This book examines the strategies that led King Philip III to extend the laurel branch to his foes. Paul Allen argues that, contrary to widespread belief, the king's gestures of peace were in fact part of a grand strategy to enable Spain to regain military and economic strength while its opponents were falsely lulled away from their military pursuits. From the outset, Allen contends, Philip and his advisers intended the Pax Hispanica to continue only until Spain was able to resume its battles - and defeat its enemies."--Jacket